Dampak Nilai Personal dan Pertimbangan Konsekuensi Masa Depan Terhadap Intensi Sustainable Entrepreneurship dalam Komunitas Muslim - Fajar Andrian Sutisna; Febrina Putri Salma; Amalia Zhalzabilla (Jurnal Bisnis dan Kewirausahaan)
Sustainable entrepreneurship is a solution to environmental problems. Intentions can encourage individuals to implement sustainable entrepreneurship. This study aims to determine the intentions of students of the Faculty of Economics and Business in sustainable entrepreneurship through thecomponents of values, attitudes, subjective norms, and behavioral control. The research method used in this study is a quantitative method with a conclusive research type. The data used are primary data with 210 respondents distributed through questionnaires. The data analysis model in this study uses Structural Equation Modeling (SEM) with Smart-PLS data processing software. The results showed that the egoistic values and CFC-I variables had a significant and positive influence on the attitude of sustainable entrepreneurship. Furthermore, the attitude and behavioral control variables have a significant direct effect on the intention of sustainable entrepreneurship. However, subjective norms have no significant effect on the intention of sustainable entrepreneurship.